From Chanakya To Modi : the evolution of India's foreign policy - Pande, Aparna (India: Harper Collins Publishers, 2017)
"Foreign policy does not exist in a cultural vacuum. It is shaped by national experience and a country s view of itself. In the case of India, the foreign policy paradigm is as deeply informed by its civilizational heritage as it is by modern ideas about national interest. Even policies that appear to be new contain echoes of themes that recur in history. The two concepts that come and go most frequently in Indian engagement with the world from Chanakya in the third century BCE to Prime Minister Narendra Modi in 2017 are autonomy and independence in decision making. There are also four trends that we can trace: messianic idealism, realism, isolationism and imperial influences ideas that have competed at one time and complemented one another at others. As India pursues modernity and seeks to exercise influence in the contemporary world, an examination of India in the context of its history and tradition is crucial. Aparna Pande's 'From Chanakya to Modi' explores the deeper civilizational roots of Indian foreign policy in a manner reminiscent of Walter Russel Mead s seminal 'Special Providence' (2001). It identifies the neural roots of India's engagement with the world outside. An essential addition to every thinking person's library."
Keywords: Kautalya; Modi -- Narendra - 1950.; India -- Foreign Relations; India -- Diplomatic Relations